Interannual and Seasonal Variability of CO2 Parameters in the Tropical Atlantic Ocean - Frederic Bonou; A. Nathanael Dossa; Adeola M. Dahunsi; Zacharie Sohou (Journal of Marine Science and Engineering)
This study examined the carbon cycling dynamics in the tropical Atlantic Ocean from 1985 to 2023, focusing on factors influencing the surface partial pressure of CO2 (pCO2), freshwater input, total alkalinity (ALK), total dissolved carbon (TCO2), and pH levels. The time series data revealed significant trends, with average pCO2 concentrations rising from approximately 350 μatm in the early 1990s to over 400 μatm by 2023. The TCO2 levels increased from about 2000 μmol/kg to 2200 μmol/kg, while ALK rose from approximately 2300 μmol/kg to 2500 μmol/kg. This increase highlights the ocean’s role as a carbon sink, particularly in areas with high biological productivity and upwelling where TCO2 also rose. This study employed Empirical Orthogonal Functions (EOFs) to identify variability modes and understand spatial patterns of pCO2. Freshwater dynamics significantly affect TCO2 concentrations, particularly in coastal regions, where pH can shift from 8.2 to 7.9, exacerbating acidification. Rising sea surface temperatures have been linked to elevated pCO2 values. These findings support the need for ongoing monitoring and effective management strategies to mitigate the impacts of climate change and ensure the sustainability of marine resources. This study documented the long-term trends in tropical Atlantic CO2 parameters linked to the North Atlantic Oscillation (NAO) and Atlantic Multidecadal Oscillation (AMO).